Successful control of menstrual cycle‐related exacerbation of inflammatory arthritis with GnRH agonist with add‐back therapy in a patient with rheumatoid arthritis. Issue 7 (20th May 2022) - Ueno, Akiko; Yoshida, Takeshi; Yamamoto, Yorito; Hayashi, Kazutoshi
Abstract: Patients with rheumatoid arthritis may demonstrate fluctuations in arthritis symptoms associated with the menstrual cycle. This is the first case report of successful control of menstrual cycle‐related exacerbation of rheumatoid arthritis with a gonadotropin‐releasing hormone agonist and add‐back therapy. A 49‐year‐old premenopausal woman experienced recurrent severe arthritis flares despite aggressive immunotherapy. Her arthritis symptoms started 10 days before her menstruation and spontaneously resolved after the initiation of menstruation. We chose a gonadotropin‐releasing hormone agonist with percutaneous estradiol gel to prevent a hypoestrogenic state and a levonorgestrel‐releasing intrauterine system to facilitate uterine protection by estrogen. Thereafter, her symptoms significantly improved without experiencing major flares. In addition, she did not demonstrate any menopausal symptoms. This case highlights that rheumatoid arthritis disease activity may be associated with the menstrual cycle, and hormonal therapy may be beneficial as an adjunct therapy for controlling premenstrual exacerbation of rheumatoid arthritis.